2015
DOI: 10.1109/tvcg.2015.2450717
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Near-Field Illumination for Photorealistic Augmented Reality with Varying Materials on Mobile Devices

Abstract: At present, photorealistic augmentation is not yet possible since the computational power of mobile devices is insufficient. Even streaming solutions from stationary PCs cause a latency that affects user interactions considerably. Therefore, we introduce a differential rendering method that allows for a consistent illumination of the inserted virtual objects on mobile devices, avoiding delays. The computation effort is shared between a stationary PC and the mobile devices to make use of the capacities availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Their factorization of the light seeks to compute the dominant light direction and color separately using spherical harmonic (SH) coefficients which is obtained by a projection onto the SH basis functions. As these functions are orthonormal, the dot product was the amount of incident light from all directions at a certain vertex [16]. Gruber et al [6] also expressed the incident light field with SH to estimate the distance of the light field which represent every incident light ray on a hemisphere from many different observers of an arbitrary geometry.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Their factorization of the light seeks to compute the dominant light direction and color separately using spherical harmonic (SH) coefficients which is obtained by a projection onto the SH basis functions. As these functions are orthonormal, the dot product was the amount of incident light from all directions at a certain vertex [16]. Gruber et al [6] also expressed the incident light field with SH to estimate the distance of the light field which represent every incident light ray on a hemisphere from many different observers of an arbitrary geometry.…”
Section: Related Workmentioning
confidence: 99%
“…Richter-Trummer et al [15] used inverse rendering which factored the texture color into incident light and the diffuse albedo color through the radiance transfer method. For more material estimation Rohmer et al [16] assumed a Lambertian environment for incident light integration over the surface of the upper hemisphere.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Placing a light probe at the virtual object location can be impractical or impossible in some situations, so other approaches focus on removing this requirement. Some approaches process information from light probes placed elsewhere in the scene to infer lighting at the virtual object location [11,37].…”
Section: Real-world Lighting Capturementioning
confidence: 99%
“…Grosch et al [14] made use of this, placing a fisheye camera at the entrance to a room to measure incoming light, and then simulating light transport within the room to add virtual content. Rohmer et al [39] demonstrated a technique combining information from multiple fisheye cameras to collect detailed lighting over a volume. Other active light probes have also been developed, such as that of Matsuoka et al [34], who used a hemispherical array of photodiodes to find the dominant light direction.…”
Section: Light Probes For Augmented Realitymentioning
confidence: 99%